2003
DOI: 10.1002/gepi.10279
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of phenotypes derived from longitudinal data: Presentation Group 1 of Genetic Analysis Workshop 13

Abstract: The participants of Presentation Group 1 used the GAW13 data to derive new phenotypes, which were then analyzed for linkage and, in one case, for association to the genetic markers. Since the trait measurements ranged over longer time periods, the participants looked at the time dependence of particular traits in addition to the trait itself. The phenotypes analyzed with the Framingham data can be roughly divided into 1) body weight-related traits, which also include a type 2 diabetes progression trait, and 2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Others who analyzed these data reported that the simulated obesity-related genes, particularly those genes affecting change over time, were very difficult to find. [Strauch, et al 2003; Yoo, et al 2003] The data creators intentionally made many of the genes challenging and perhaps even impossible to find. [Daw, et al 2003] Although the power was low, the sumLINK and sumLOD statistics consistently outperformed the HLOD in identifying the minor genes.…”
Section: Discussionmentioning
confidence: 99%
“…Others who analyzed these data reported that the simulated obesity-related genes, particularly those genes affecting change over time, were very difficult to find. [Strauch, et al 2003; Yoo, et al 2003] The data creators intentionally made many of the genes challenging and perhaps even impossible to find. [Daw, et al 2003] Although the power was low, the sumLINK and sumLOD statistics consistently outperformed the HLOD in identifying the minor genes.…”
Section: Discussionmentioning
confidence: 99%
“…However, this approach ignores rich information in the longitudinal structure and may not detect genes affecting the time varying features of a trait. Strauch et al (2003) reviewed several two-step methods: the first step is either to take the average of trait measurements on a subject or to fit a longitudinal model without consideration of genetic markers or family structures; the second step is to perform genetic analysis on one or more summary statistics derived from the first step. This method may be improved by a joint approach that fits longitudinal and genetic parameters simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Heritability of BP traits has been shown to be age-dependent too [6,12]. Only a few studies deal with BP longitudinal heritability analysis [12,[23][24][25][26][27][28][29][30][31][32][33][34]; the family dataset of these studies is mainly derived from the Framingham Heart Study. The largest numbers of studies dealing with BP heritability estimates are based on cross-sectional family studies.…”
Section: Introductionmentioning
confidence: 99%